Permanent evolution selected essays on literature, theory and film - Tynjanov, Jurij Nikolaevič 1894-1943 (Academic Studies Press, 2019)
Theory through history - then. Dostoevsky and Gogol (toward a theory of parody) ; Tyutchev and Heine ; The ode as an oratorical genre ; On the composition of Eugene Onegin -- Theory through history - now. Literary fact ; Interlude ; On Khlebnikov ; Film - word - music -- Evolutions in literature and film. On the screenplay ; On plot and fabula in film ; The foundations of film ; On literary evolution -- Epilogue. Problems of the study of literature and language (with Roman Jakobson) ; On FEX ; On Mayakovsky: In memory of the poet ; On parody
Includes selected works from the author's "Arkhaisty i novatory" and "Poėtika, istorii͡a literatury, kino"
Includes bibliographical references and index
Keywords: Film; Literatur; Literaturwissenschaft; Russisch; Russian literature / History and criticism / Theory, etc; Motion pictures / History